ANALYSIS OF LEGAL STATUS, LEGAL PROTECTION OF MARKS THAT HAVE BEEN REGISTERED (STUDY OF DECISION NUMBER 03/PDT.SUS-MEREK/2015/PN NIAGA MEDAN) - Lenny Mutiara Ambarita; Van Lodewijk Purba; Muhammad Fadly Nasution (RADJA PUBLIKA, 2022)
The purpose of this study is to analyze the legal position and legal protection of trademarks that have been registered (Study of Decision Number 03/Pdt.Sus-MEREK/2015/PN Niaga Medan). The type of research used in writing this thesis is normative juridical research. Normative juridical research,